Parenthesis and Ellipsis: Cross-Linguistic and Theoretical Perspectives - Kluck, Marlies; Ott, Dennis; de Vries, Mark (De Gruyter, 2014)
This volume presents a cross-section of research addressing the interaction of two prominent areas in linguistic theory: parenthesis and ellipsis. The contributions address various theoretical questions raised by 'incomplete' parenthetical constituents, covering a diverse empirical domain and various subfields of linguistics.